(untitled) - Pataki, Allison; Pataki, Owen (New York, 2017)
"From the courtrooms to the battlefields to the alleyways of Paris, with cameos from infamous figures in French history like Robespierre and Napoleon, the Patakis craft a sweeping, action-packed novel of the French Revolution as it has never been seen before. Three years after the storming of the Bastille, Paris is emboldened with the ideals of liberty, equality, and fraternity. The monarchy of King Louis and Marie Antoinette has been dismantled and a new nation, for the people, is rising up in its place. Jean-Luc, a young optimistic lawyer, moves his wife, Marie, and their infant son from their comfortable life in Marseilles to Paris, inspired by a sense of duty to contribute to the new order. André, the son of a former wealthy Duke, sheds his privileged upbringing to fight in the unified French Army with his roguish brother, Remy. Sophie, a descendent of a wealthy aristocratic family and niece of a militant uncle, embarks on her own fight for independence. But underneath the glimmer of hope and freedom, chaos threatens to undo all the progress of the revolution and the lives of these compatriots become inextricably linked. As the demand for justice, aided by the new invention of the guillotine, breeds instability, creates enemies out of compatriots, and fuels a constant rush of blood in the streets, Jean-Luc, Andre, and Sophie are forced to question the sacrifices made for the revolution and determine what is right in the midst of a struggling society"--Provided by publisher.
Keywords: Fiction; Fiction; Widows; Fiction; Interpersonal relations; Social conflict; France; History; Revolution, 1789-1799; Fiction; Paris (France); History; 1789-1799; Fiction; Historical fiction